STRATEGI KOMUNIKASI PROGRAM CSR PT. PERTAMINA PATRA NIAGA INTEGRATED TERMINAL SURABAYA (ANALISIS TEORI SMITH & ROLAND) - Indah Mawarni; Dhimam Abror; Widya Desary Setya Wardhani (LPPM Stikosa - AWS, 2025)
Corporate Social Responsibility (CSR) is a manifestation of a company's social responsibility in creating a balance between business, community, and environmental interests. PT. Pertamina Patra Niaga Integrated Terminal Surabaya, as one of the strategic operational units, strives to implement Corporate Social Responsibility (CSR) through various programs aimed at improving the welfare of the surrounding community. This study aims to analyze the implementation of the company's CSR Program, covering aspects of planning, implementation, and its impact on the community and the company's image. The method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results of the study show that the implementation of Corporate Social Responsibility (CSR) has been effective in providing positive impacts on the surrounding community, particularly through empowerment and environmental quality improvement programs. CSR is not only seen as a form of fulfilling corporate obligations, but also as a manifestation of moral commitment to improving social welfare and maintaining environmental sustainability. This study found that appropriate communication strategies, public relations support, and active community involvement are important factors in the successful implementation of CSR Programs. In addition, CSR implementation also contributes to improving the company's image and strengthening harmonious relationships with the community as key stakeholders. These findings confirm that CSR plays a strategic role in supporting sustainable development and providing added value to both companies and communities.